GEORGIA-SOUTH OSSETIA: A PRELUDE TO WAR Did Economic Assistance Strengthen Competing Spoilers in Georgian-South Ossetian Conflict? - GOGIA, Giorgi (CENTRAL ASIA AND THE CAUCASUS, 2009)
Sixteen years after the Sochi agreements an uneasy truce between Georgia and South Ossetia gave way to renewed violence in August 2008. The protracted peace process with lengthy and futile negotiations led to few agreements between the conflicting sides, which were often faulted at the implementation phase. Material and human costs of a failed peace process were huge: hundreds of civilian deaths, thousands of wounded, tens of thousands of people displaced, and millions of Euros spent on rehabilitation projects by local and international actors vanished within days. With millions of aid money poured into Georgia for conflict prevention purposes prior to 2008, it is only legitimate to ask whether aid could make things worse and contribute to renewed violence, or to a lack of the sides’ interest in peaceful conflict settlement. Much has been written on political, geopolitical and military aspects of the Georgian-South Ossetian conflict and failed peace settlement that led to renewed hostilities in 2008. This article, however, looks at how aid (intentionally or unintentionally) contributed to dividing lines in the Georgian-South Ossetian conflict and strengthened competing spoilers in the settlement process. It argues that economic rehabilitation projects, supported by competing actors, in the conflict zone fed into the dividing lines between the local Georgian and Ossetian communities, and the international community failed to bridge the widening gaps between them. With the ceasefire signed in the early 1990s and stalled peace talks, many observers have branded the Georgian-South Ossetian conflict as frozen. However, the August 2008 conflict between Russia and Georgia over South Ossetia once again demonstrated the importance of the consolidation of conflict settlement and necessity to deal with threats to peacebuilding. Although the negotiation process has been halted since 2006, it would be a mistake to call the Georgian-Ossetian conflict a frozen one. Despite low level of violence and frequent security incidents in the conflict zone, the ceasefire largely held until the summer of 2004, when Tbilisi’s antismuggling operation in the conflict zone led to dozens of casualties and stopped short of the real warfare. Since then Tbilisi has been trying to alter the status quo in the negotiations and peacekeep ing formats, which it, not without merits, saw as disadvantageous. These efforts intensified with the Georgian leadership backing up an “alternative” de facto government of Dmitri Sanakoev in South Ossetia in November 2006. Tbilisi provided Sanakoev, who controlled Georgian enclaves in South Ossetia, with strong financial and political support, putting him in charge of a temporary administration established in May 2007. Attempts were made to include Sanakoev in the established negotiations processes.